The assessment of ongoing community-based interventions to prevent obesity: lessons learned - Gubbels, Jessica S (BMC Public Health, 2015)
BACKGROUND: The assessment of real-life, community-based interventions to tackle obesity is an important step in the development of effective policies. Especially multi-level interventions have a high likely effectiveness and potential reach in counteracting the obesity epidemic. Although much can be learned from these initiatives, performing an evaluation of such interventions is challenging. The aim of the current article is to provide a descriptive overview of the data collection process and general results of an assessment of ongoing multi-level obesity prevention community interventions for adults in Europe, and the lessons learned from this effort. METHODS: The data collection was divided into two main phases: a) finding the ongoing obesity prevention interventions by contacting key informants in each of the European Union countries and the European Economic Area, and searching existing databases; and b) collecting detailed information (including the reach, effectiveness, adoption, implementation and maintenance (RE-AIM)) of the selected interventions using questionnaires for informants in each of the interventions. RESULTS: A total of 78 interventions from 24 European countries were included in the final sample. The number of identified interventions varied greatly per country. The interventions covered various implementation levels (national, regional or local) and determinants (physical, sociocultural, economic, political), mostly addressing both nutrition and physical activity behaviours. CONCLUSIONS: We found that many multi-level obesity prevention interventions among adults are currently active in Europe, although we found relatively few in Southern and Eastern Europe. Identifying interventions and obtaining detailed information proved to be a difficult, time consuming and painstaking process. We discuss some of the reasons why this might be the case and present recommendations based on our experiences. We suggest that future research uses a step-wise approach, keeping participant burden to a minimum. The use of personalised and tailored strategies is recommended, led by researchers who exercise flexibility, tact and patience during the data collection process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1563-2) contains supplementary material, which is available to authorized users.